Minimal-invasive enhancement of auditory perception by terahertz wave modulation - Tan, Xiaoxuan; Wu, Kaijie; Liu, Shuang; Yuan, Yifang; Chang, Chao; Xiong, Wei (Nano research, 2022)
Hearing impairment is a common disease affecting a substantial proportion of the global population. Currently, the most effective clinical treatment for patients with sensorineural deafness is to implant an artificial electronic cochlea. However, the improvements to hearing perception are variable and limited among healthy subjects. Moreover, cochlear implants have disadvantages, such as crosstalk derived from the currents that spread into non-target tissue between the electrodes. Here, in this work, we describe terahertz wave modulation, a new and minimally invasive technology that can enhance hearing perception in animals by reversible modulation of currents in cochlear hair cells. Using single-cell electrophysiology, guinea pig audiometry, and molecular dynamics simulations, we show that THM can reversibly increase mechano-electrical transducer currents (∼ 50% higher) and voltage-gated K + currents in cochlear hair cells through collective resonance of −C=O groups. In addition, measurement of auditory brainstem response (ABR) in guinea pigs treated with THM indicated a ~ 10 dB increase in hearing sensitivity. This study thus reports a new method of highly spatially selective hearing enhancement without introducing any exogeneous gene, which has potential applications for treatment of hearing disorders as well as several other areas of neuroscience.